Perceptions of Preparers from Romanian Banks Regarding IFRS Application - Madalina Girbina; Mihaela Minu; Stefan Bunea; Marian Sacarin (Journal of Accounting and Management Information Systems (JAMIS), 2012)
Starting 1 January 2012, credit institutions are required to apply the International Financial Reporting Standards (IFRS) as basis of accounting for the preparation of the individual financial statements. Regulatory reforms were done and banks prepared to face the transition process. In this context, the aim of our study is to investigate, the perceptions of the main actors from banks (responsible with the transition process) on the cost and benefits involved by the use of IFRS as reporting standards (implementation strategy used by some banks before 2012) and on the peculiarities related to the application of IFRS as accounting basis (each transaction or event being recorded following IFRS requirements) immediately after 1st January 2012. We intended to investigate also if the transition process changed the attitude of banks towards the application of IFRS. We observed that preparers still have a positive attitude towards the application of IFRS considering that the cost benefit report is a positive one. Not all preparers are convinced that the conversion will lower the cost of capital. The complex nature of IFRS, the insufficient application guidance and the necessity to adapt to frequent changes of IFRSs were considered as difficulties related to IFRS reporting. Double reporting costs reduction and eliminating confusions by publishing two sets of financial statements were considered unanimously benefits of using IFRS as basis of accounting. It resulted that most preparers are concerned about the costs involved by the modification of internal evidence systems, the necessity to satisfy multiple reporting requirements (accounting, prudential and fiscal), the impact on prudential indicators and the insufficient resources allocated to this process. The most important cost was related to the modification of actual IT systems. The impairment methodology described by IAS 39 was rated as most challenging by preparers.
Keywords: M41; 650; IFRS; financial reporting; banks; accounting basis; national regulations